Assessing vulnerability and adaptation strategies of forest dependent people to climate change in the Mid-hills of Nepal - Acharya, K.; Tiwari, K. R.; Timilsina, Y. P.; PC, S (Banko Janakari, 2015)
Climate change is now recognized as one of the most serious challenges facing the world– its people, the environment and its economies. Rural people are more vulnerable to the effects of climate change due to its high dependence on climate-sensitive sectors like glaciers, agriculture and forestry, and its low financial adaptive capacity. This study was carried out with the aim of assessing and documenting vulnerability and adaptation strategies of forest-dependent people to climate change effects in Mid-hills of Nepal. Primary data were collected from household survey, interview with key informants, and focused group discussion. The results showed that the average annual rainfall was decreasing at the rate of 18.02 mm whereas the average annual mean temperature was increasing at the rate of 0.07°c per year. The major climatic hazards, of the study area, identified were long drought and landslide. The chi-square test shows that the poor forest-dependent people are more vulnerable to long drought, landslide and floods as compared to the rich rural people. Indigenous adaptation practices such as cultivation of vegetables and other crops that are less susceptible to droughts, and rearing of hybrid-varieties of livestock are mostly used to cope with climate change impacts. The results indicate that 15% of the respondents have changed their cropping pattern from paddy to off-seasonal vegetables crops because of more income from vegetable farming. Raising awareness and sharing information as well as increasing income from farming among the locals by applying new technologies should be done in order to build their capacity to cope with climate change impact. Banko Janakari, A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page: 55-62